استراتيجية مقترحة قائمة على عملية التصميم الهندسي EDP لتنمية بعض عادات العقل الهندسية EHoM لدى أطفال الروضة - المنير، راندا عبدالعليم أحمد (رابطة التربويين العرب, 2018)
هدفت هذه الدراسة إلى التحقق من فاعلية استراتيجية مقترحة قائمة على عملية التصميم الهندسي في تنمية بعض عادات العقل الهندسية لدى أطفال الروضة. واشتملت عينة الدراسة على (65) طفلا وطفلة من أطفال المستوى الثاني برياض الأطفال (5 – 6) سنوات، بالروضتين الملحقتين بمدرستي دوحة الزمان الابتدائية، والزهور الابتدائية بمدينة الإسماعيلية، مقسمين إلى مجموعتين: ضابطة قوامها (32) طفلا وطفلة، وتجريبية قوامها (33) طفلاً وطفلة. واستخدمت الدراسة عددا من الأدوات تمثلت في: استبيان حول قائمة عادات العقل الهندسية ومعاييرها ومؤشراتها المناسبة لأطفال الروضة (إعداد الباحثة)، استبيان حول قائمة الخطوات/ العمليات الفرعية لعملية التصميم الهندسي ومعاييرها المناسبة لتدريب أطفال الروضة على عادات العقل الهندسية (إعداد الباحثة)، استبيان حول الإطار العام للاستراتيجية المقترحة القائمة على عملية التصميم الهندسي لتنمية عادات العقل الهندسية لدى طفل الروضة (إعداد الباحثة)، كما تم استخدام أداتين للضبط التجريبي، وهما اختبار المصفوفات المتتابعة الملونة لرافن (تقنين/ علي، 2016)، مقياس المستوى الاجتماعي الاقتصادي للأسرة (إعداد الشخص، 2006). وتمثلت مادة المعالجة التجريبية في برنامج قائم على الاستراتيجية المقترحة، اشتمل على (30) نشاطاً لتنمية عادات العقل الهندسية لدى أطفال الروضة (إعداد الباحثة). وأوضحت نتائج الدراسة وجود فرق ذو دلالة إحصائية عند مستوى (0.01) بين متوسطي درجات أطفال المجموعتين الضابطة والتجريبية في التطبيق البعدي لمقياس تقدير عادات العقل الهندسية على كل بعد (تفكير النظم، وإيجاد المشكلات، والتصور البصري، والتحسين، والابتكار، والتفاؤل، والتكيف، والتعاون، والتواصل، والانتباه إلى الاعتبارات الأخلاقية) ومجموعة الأبعاد لصالح أطفال المجموعة التجريبية، ووجود فرق ذو دلالة إحصائية عند مستوى (0.01) بين متوسطي درجات أطفال المجموعة التجريبية، في التطبيقين القبلي والبعدي لمقياس تقدير عادات العقل الهندسية (على كل بعد ومجموع الأبعاد) لصالح التطبيق البعدي. وعدم وجود فرق ذو دلالة إحصائية بين متوسطي درجات أطفال المجموعة التجريبية، في القياسين البعدي والتتبعي لعادات العقل الهندسية.
This study aimed to investigate the effectiveness of a suggested strategy based on Engineering Design Process (EDP) for developing some Engineering Habits of Mind (EHoM) in kindergarteners. The study's sample consisted of (65) children enrolled in the second level of kindergarten (5-6) years old, from Dawhat Al Zaman and Al Zuhur Elementary Schools in Ismailia city, assigned to a control group (n = 32) or an experimental group (n = 33). The study used a group of tools a followings: A questionnaire about a list of EHoM, its standards and indicators for kindergarteners (Prepared by the researcher), A questionnaire about a list of EDP steps and its standards that appropriate for training kindergartners on EHoM (Prepared by the researcher), A questionnaire about the framework of the suggested strategy based on EDP for developing some EHoM in kindergarteners (Prepared by the researcher), Kindergarten EHoM Rating Scale (Prepared by the researcher). Two tools were used for Experimental control: Raven's Colored Progressive Matrices (Standardized by Ali, 2016) and Family Social Economic Level Inventory (Prepared by Elshakhs, 2006). The experimental treatment material is a program based on the suggested strategy, included (30) activities for developing EHoM in kindergarteners(Prepared by the researcher). The study's findings suggested that there is significant statistical difference at (.01) level between the means score of control and experimental groups children in the posttest of EHoM Rating Scale in each domain (systems thinking, problem-finding, visualizing, improving, creativity, optimism, adapting, collaboration, communication, and attention to ethical considerations) and the sum of them in favor of the experimental group children, there is significant statistical difference at (.01) level between the means score of experimental group children in the pretest and posttest of EHoM Rating Scale (in each domain and the sum of them) in favor of the posttest, and there is no significant statistical difference between the means score of experimental group children in the posttest and follow up test of EHoM.
Keywords: الاستراتيجيات التعليمية -- التصاميم الهندسية -- العادات العقلية -- أطفال الروضة